Strengthening fiscal risk management of government guaranteed loans in Vietnam improving public expenditure quality program. (Metro Manila, Philippines Asian Development Bank, 2017)
This brief summarizes the findings of policy advice prepared by ADB for the Viet Nam Ministry of Finance to support improvements in the fiscal risk management of government loan guarantees.
Keywords: Public administration -- Vietnam; Fiscal policy -- Vietnam; Electronic books